2011
DOI: 10.1007/s00109-011-0796-5
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte α-kinase is a gout-susceptible gene involved in monosodium urate monohydrate-induced inflammatory responses

Abstract: The molecular functions and pathophysiologic role of the lymphocyte α-kinase gene (ALPK1) in gout are unknown. We aimed to examine ALPK1 expression in patients with gout and investigate its role in monosodium urate monohydrate (MSU)-induced inflammatory responses. Microarray data mining was performed with six datasets containing three clinical gout and three volunteer samples. Real-time quantitative polymerase chain reaction (qPCR) assay was used to profile ALPK1 mRNA expression in 62 independent samples. RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 34 publications
2
43
0
1
Order By: Relevance
“…rs2074381 of ALPK1 was significantly associated with CAD and ischemic stroke, with the GG genotype being protective against these conditions. These previous observations (27,41,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) and our present results suggest that ALPK1 may contribute to the development of CAD and ischemic stroke through the acceleration of vascular inflammation, although the molecular mechanisms underlying the role of rs2074381 of ALPK1 in the pathogenesis of CAD and ischemic stroke remain unknown.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…rs2074381 of ALPK1 was significantly associated with CAD and ischemic stroke, with the GG genotype being protective against these conditions. These previous observations (27,41,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) and our present results suggest that ALPK1 may contribute to the development of CAD and ischemic stroke through the acceleration of vascular inflammation, although the molecular mechanisms underlying the role of rs2074381 of ALPK1 in the pathogenesis of CAD and ischemic stroke remain unknown.…”
Section: Discussionsupporting
confidence: 78%
“…ALPK1 functions in apical transport by phosphorylating myosin 1a in epithelial cells and is indicated in the regulation of intracellular trafficking processes by phosphorylation (40). ALPK1 may act synergistically with monosodium urate monohydrate crystals to promote the production of proinflammatory cytokines through the activation of nuclear factor-κB and mitogen-activated protein kinase (extracellular signal-regulated kinase 1/2 and p38) signaling in cultured human embryonic kidney 293 (HEK293) cells, suggesting that ALPK1 may contribute to the inflammatory process associated with the development of gout (41). Our previous GWAS for chronic kidney disease showed that the overexpression of ALPK1 resulted in upregulation of the expression of cystatin C in cultured HEK293T cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Those observations suggested that the correlation of ALPK1 to MI may be mediated by the effects of cystatin C on the development of vascular inflammation. Therefore, those observations (17)(18)(19)(21)(22)(23)(24) suggested that ALPK1 may contribute to the development of MI through the acceleration of vascular inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…ALPK1 is expressed in various human tissues, including the heart and kidney (15) and was shown to be crucial in protein sorting and polarization in epithelial cells (16). ALPK1 may act synergistically with monosodium urate monohydrate crystals to promote the production of proinflammatory cytokines through the activation of nuclear factor-κB and mitogen-activated protein kinase (ERK1̸2 and p38) signaling in cultured HEK293 cells (17), indicating that ALPK1 may contribute to the inflammatory process associated with the development of gout. Since the onset of MI is likely precipitated by activated inflammation at atherosclerotic plaques in the coronary arterial wall (18,19), the association of ALPK1 to MI may be attributable to its effect on vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…ALPK1 may act synergistically with monosodium urate monohydrate crystals to promote the production of proinflammatory cytokines through the activation of nuclear factor-κB and mitogen-activated protein kinase (extracellular signal-regulated kinase 1/2 and p38) signaling in cultured HEK293 cells, suggesting that ALPK1 may contribute to the inflammatory process associated with the development of gout (39).…”
Section: Discussionmentioning
confidence: 99%